RECONCEPTUALIZING ISLAMIC STUDENT WELL-BEING THROUGH TARBAWI HADITH: A THEMATIC LIBRARY-BASED ANALYSIS - Setiady, Dicky; Askar, Romlah Abubakar (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
The well-being of students in the pursuit of knowledge is a multidimensional issue encompassing spiritual, academic, psychological, social, physical, and economic aspects. In Islamic education, this well-being is not solely determined by worldly factors but emphasizes a balance with spiritual and eschatological values. This study aims to reconceptualize Islamic student well-being through a thematic analysis of tarbawi (educational) hadiths. Employing a qualitative method with a library-based research design, data were analyzed from primary and secondary sources related to educational hadiths and Islamic well-being. The findings reveal that tarbawi hadiths contain integral principles of well-being, structured into six key dimensions: spiritual, academic, psychological, social, physical, and economic. These insights offer a new conceptual framework for understanding student well-being within a holistic Islamic educational paradigm. Kesejahteraan mahasiswa dalam menuntut ilmu merupakan isu multidimensional yang mencakup aspek spiritual, akademik, psikologis, sosial, fisik, dan ekonomi. Dalam konteks pendidikan Islam, kesejahteraan ini tidak hanya ditentukan oleh faktor duniawi, tetapi juga menekankan keseimbangan dengan orientasi ukhrawi. Penelitian ini bertujuan untuk merumuskan kembali konsep kesejahteraan mahasiswa Muslim (Islamic student well-being) melalui pendekatan tematik terhadap hadis-hadis tarbawi. Menggunakan metode kualitatif dengan desain studi kepustakaan, data dianalisis dari berbagai literatur primer dan sekunder mengenai hadis pendidikan dan konsep kesejahteraan Islam. Hasil penelitian menunjukkan bahwa hadis-hadis tarbawi memuat prinsip-prinsip kesejahteraan yang integral, mencakup enam dimensi utama: spiritualitas, akademik, psikologis, sosial, fisik, dan ekonomi. Temuan ini memberikan kerangka konseptual baru dalam memahami kesejahteraan mahasiswa dalam kerangka pendidikan Islam yang komprehensif.